أستخدام أسلوب البرمجة الخطية على المحاصيل الزراعية باستخدام ستراتيجيات القرار المتعدد - علوان, فارس مهدي; بطيخ, عباس حسين (Journal of Economics and Administrative Sciences, 2008)
The idea of this study depends on determining the demand of water to products of aslected project, and determining transformation wastes according to constant scientific formula and measuring value (the depended) to reach the water needed and give the amount of waste in water and additional areas that can be agricuitured if the right administration and possibilities of exploiting water well are available